De Novo Germline and Somatic Variants Convergently Promote Endothelial-to-Mesenchymal Transition in Simplex Brain Arteriovenous Malformation. Issue 9 (17th September 2021) - Li, Hao; Nam, Yoonhee; Huo, Ran; Fu, Weilun; Jiang, Biaobin; Zhou, Qiuxia; Song, Dong; Yang, Yingxi; Jiao, Yuming; Weng, Jiancong; Yan, Zihan; Di, Lin; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: Brain arteriovenous malformations (bAVMs) are abnormal entanglement of blood vessels in brain, with direct connections from arteries to veins, lacking functional capillary bed. Although several somatic mutations were reported, the molecular mechanism and genetic disposition of bAVM remain poorly understood. Objective: We aim to identify transcriptional anomalies and critical functional pathways in bAVM lesions and explore their association with key de novo germline and somatic variants in bAVM patients. Methods and Results: We established a comprehensive bAVM dataset from 269 patients, by performing single-cell sequencing of 17 bAVM lesions, whole-exome sequencing of germline DNA from 60 case-unaffected-parental trios, and genomic/transcriptomic sequencing of 231 bAVM lesions. We found abnormal expression of endothelial and mesenchymal markers in bAVM at both bulk and single-cell level, which was validated by flow cytometric analysis and immunofluorescence staining, suggesting an involvement of endothelial-to-mesenchymal transition (EndMT) process in AVM (arteriovenous-malformation). Using data from the 60 trios, we identified nonsynonymous de novo germline mutations affecting 46 genes, including EXPH5 (detected in 2 independent cases), and vessel-related genes, such as EPAS1 and ENG . Interestingly, knockdown of epas1 in zebrafish embryo showed AVM-like phenotype exclusively in brain. Subsequent computational and experimental analyses demonstrated that expression of genes affected by de novo germline mutations was enriched in vascular cell types and was involved in EndMT-relevant behaviors including cell migration, angiogenesis, and cell marker transition. Moreover, we detected somatic KRAS mutations in 129 of 179 (72%) cases and showed that KRAS mutations were associated with bleeding as the first symptom ( P =0.0072). Following experimental studies demonstrated that KRAS mutations independently regulated EndMT features, consolidating the involvement of EndMT in this disease. Lastly, we showed that lovastatin reversed EndMT features in vitro and ex vivo. Conclusions: Our results suggest the convergent role of de novo germline mutations and somatic mutations in regulating EndMT in bAVM and provided a potential therapeutic option.